Efek Pemberian Antioksidan Vitamin C dan E terhadap Kualitas Spermatozoa Tikus Putih Terpapar Allethrin - Christijanti, Wulan; Utami, Nur Rahayu; Iswara, Arya (Biosaintifika: Journal of Biology & Biology Education, 2010)
Allethrin  is  one  of  synthetic  pyrethroid types which  is  used  in many mosquito repellents and has toxic potential. The aim of this research was to examine the infl uence of vitamin C and E antioxidant activity to the sperm quality of allethrin-induced albino rats. This research used a post-test randomized design. The population of the research were  8  hr/day  allethrin-induced male  albino  rats. The  sample  of  the  research was allethrin-induced male albino rats which were divided into 4 groups, i.e. group I was the control group, group II was the group treated with 1.8 mg vitamin C per day, group II was the group treated with 1.44 mg vitamin E per day, and group IV was treated with a combination of 1.8 mg vitamin C per day and 1.44 mg vitamin E per day. The duration of the treatment was 45 days. The sperm sample was taken in day 46. The data consisted of sperm count or amount, sperm motility, sperm viability, and sperm morphology, and then was analyzed with ANOVA followed by BNT. The result showed that vitamin C and E antioxidants signifi cantly infl uenced the the sperm quality of the 45-day mosquito repellent-induced rats. Overall, the allethrin-induced albino rats treated with vitamin C and E antioxidants were better in maintaining the sperm quality than single treatment of vitamin antioxidants.Keywords: allethrin, vitamin C, vitamin E, antioxidant, sperm  quality.